Avaliação de componentes da dieta de Pontoporia blainvillei Gervais & d Orbigny, 1844 (Cetacea, Pontoporiidae) como possíveis hospedeiros intermediários ao parasitismo por helmintos - Silveira, Tony Leandro Rezende da (2014)
Pontoporia blainvillei is a cetacean popularly know in Brasil as toninha. Its distribution is restrict for estuarine and coastal waters of south-west of Atlantic. Studies of gastrintestinalparasitology of toninhas indicate a component community formed for less species, including nematodes, trematodes and acantocephalans. However, despite knowing that the course of infection is the ingestion of infected prey, intermediate hosts are unknown. The toninhas s diet is composed mainly for fishes, squids and shrimps. Many of these fishes in various areas of distribution of the cetacean have been reported with parasites that attack the species in some stage of development. However, larval forms of the trematode Synthesium pontoporiae and the acantocephalan Bolbosoma turbinella were not identified in any of the food items of P. blainvillei. The present study aimed to evaluate three components of the diet of P. blainvillei as possible sources transmission of parasitiasis. Fifty specimens of Doryteuthis sanpaulensis; forty-three specimens of Paralonchurus brasiliensis and fifty specimens of Trachurus lathami were necropsied. The organs were individually, washed in tamis (150μm) and examined under a stereomicroscope. Helminths were collected, counted, fixed in AFA, stained with Delafield s hematoxylin or Gomori s trichrome, clarified in Amman s lactophenol or Beech creosote and mounted on slides. Parasitological indices were calculated. None of the food items analyzed showed infection by metacercariae of S. pontoporiae. Helminths found in D. sanpaulensis did not have records of infection of P. blainvillei. Cistacanths of C. australe were found in the coelomic cavity and mesentery of P. brasiliensis (P=53,49%; IMI=6,74) and of T. lathami (P=4%; IMI=1,50). Cistacanths of B. turbinella were on same sites of T. lathami (P=14%; IMI=2,14). Paralonchurus brasiliensis and T. lathami are recorded in this study as new paratenics hosts for C. australe, as well as T. lathami is to B. turbinella. In addition to the parasites that infect P. blainvillei, the nematodes Hysterothylacium sp., Dichelyne (D.) spinicaudatus and Procamallanus pereirai, and trematodes Diphterostomum brusinae, Opecoeloides catarinensis, O. stenosomae, Pachycreadium gastrocotylum, Aponurus laguncula, A. pyriformis and Lecithochirum sp. are registered as members of the component community of P. brasiliensis and five new records of parasitism on fish and a new record of parasite species to brazilian waters. The use of nematodes as biomarkers for distinguishing the populations of P. brasiliensis is discussed. Through the present study more about the ecology and parasitology of final and paratenic hosts were revealed, as well as aspects of the biology of parasites, contributing to the knowledge about the marine biology of the south Atlantic.